2019
DOI: 10.18865/ed.29.4.559
|View full text |Cite
|
Sign up to set email alerts
|

The Burden of Hypertension and Diabetes in an Emergency Department in Northern Tanzania

Abstract: Introduction: Little is known about the burden of hypertension and diabetes on emergency department (ED) utilization and hospitalizations in sub-Saharan Africa.Methods: A retrospective review of adult ED patients in northern Tanzania was performed from September 2017 through March 2018. Hypertension was defined as documented diagnosis of hypertension or blood pressure ≥ 140/90 mm Hg. Diabetes was defined as documented diagnosis of diabetes mellitus or random glucose ≥ 200 mg/dL.Results: Of 3961 adult ED patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0
7

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(26 citation statements)
references
References 29 publications
(43 reference statements)
1
18
0
7
Order By: Relevance
“…This is the rst study investigating vascular associations for HAND in older PLWH in SSA. Hypertension was less prevalent than rates reported in Tanzanian rural elders (69%, age ≥ 70) [50] and urban older adults (48%, age ≥ 55) [51] , but broadly similar to adult ED attendees (34.3%) [52] and SSA-wide estimates for adults of all ages (30%) [53] . This is surprising given that in both high-and low-income settings older PLWH and those receiving c-ART appear to have higher hypertension prevalence [54,55] .…”
Section: Prevalence Of Vrfs and Vascular Eodsupporting
confidence: 59%
“…This is the rst study investigating vascular associations for HAND in older PLWH in SSA. Hypertension was less prevalent than rates reported in Tanzanian rural elders (69%, age ≥ 70) [50] and urban older adults (48%, age ≥ 55) [51] , but broadly similar to adult ED attendees (34.3%) [52] and SSA-wide estimates for adults of all ages (30%) [53] . This is surprising given that in both high-and low-income settings older PLWH and those receiving c-ART appear to have higher hypertension prevalence [54,55] .…”
Section: Prevalence Of Vrfs and Vascular Eodsupporting
confidence: 59%
“…A Hipertensão Arterial Sistêmica (HAS) e o Diabetes Mellitus (DM) configuram as principais causas de morte e invalidez em todo o mundo 1,2 . Estima-se que até 2050 seis países de renda média, entre eles o Brasil, apresentarão mudanças demográficas importantes, com aumento considerável do número de adultos que necessitarão de tratamento para doenças crônicas 3 .…”
Section: Introductionunclassified
“…A study done in states that hypertension in sub-Saharan Africa is a widespread problem of immense economic importance because of its high prevalence in urban areas, its frequent under diagnosis, and the severity of its complications [11] . In Tanzania for example, a study done in Northern Tanzania in 2019 showed the complications such as heart failure, stroke, renal failure, ischemic heart disease, chronic kidney disease [12] .…”
Section: Introductionmentioning
confidence: 99%